A randomised prospective trial to compare the efficacy of bolus versus continuous nasogastric feeding in paediatric intensive care. (24th May 2012) - Kamath, P; Longden, J; Stack, C; Easaw, S; Mayer, A
Abstract : Objective: To compare bolus versus continuous nasogastric feeding in a tertiary paediatric intensive care unit (PICU). The outcome measures were: time to achieve maximal nutritional requirement by volume of feed and identify frequency of adverse events. Design: Prospective randomised study. Patients: 87 patients were recruited in the 22 months study period between April 2006 and February 2008. 76 patients were included for analysis. Measures and main results: Following ethical approval and informed consent, eligible admissions to a tertiary PICU from April 2006 to February 2008 were prospectively randomised and enrolled into the study. Gastrostomy feeding, use of motility drugs, gastro-oesophageal reflux and gastrointestinal surgery were exclusion criteria. Patients were randomised to receive either 3 hourly bolus feeds or continuous feeding over 21 hours per day, for a 48 hour study period. Nasogastric (NG) tubes were aspirated 3 hourly and the gastric residual volume recorded (GRV). The protocol was designed to give equal feed volume in a 24 hr period. Intolerance was defined as GRV more than 125% of feed administered. 76 patients were analysed (1.2:1, M: F) median age 11.6 (2.8-49.0) months and weight 10 (4.5-16.2) kg. Bolus group subjects achieved maximal feed potential by 21 hours (18.6 to 25, 95% CI), the continuous group required 27 hours (19.5 to 30, 95% CI, p=0.034). PIM2 scores, sedation, muscle relaxant or inotropes usage between groups were comparable. There was no statistically significant difference in the incidence of adverse events (bolus n=3 and continuous n=4, p=0.71). Data expressed as Median (interquartile range), Mann Whitney's test and Fisher's exact test were used to test for associations. Conclusion: This study suggests that bolus feeding methods may be more beneficial, in achieving maximal nutritional requirements earlier, when compared to continuous feeds. The risk of aspiration of aspiration or vomiting is low with both feeding techniques.